Pigs, people, pathogens: Health and multispecies relations in central Uganda - Thompson, R.G. (University of Edinburgh, 2019)
This thesis describes the convergence of health and sickness in pigs and people in central Uganda. Drawing on thirteen months of ethnographic research, the chapters of this thesis trace diseases along the pig supply chain as they move from pig bodies on farms, into carcasses in slaughterhouses, meat in pork joints, and into human bodies in clinics and hospitals. Throughout this thesis, I argue that while the health of people was often dependent upon the lives of pigs, the development of beneficial relationships between pigs and people masked the emergence of pathogens which had the potential to threaten lives. One such pathogen was the neglected zoonotic parasite, Taenia solium taeniasis/cysticercosis (TSTC). With a focus on TSTC, I show how people along the supply chain did not always understand pig and human sickness in terms of pathogens. I suggest, therefore, that the visibility of pathogens along the supply chain is contingent upon networks that create and sustain their existence. Central to my argument is the concept of enactment, or the notion that objects, diseases, and bodies are not fixed, stable entities but are instead made through practices. While previous studies have considered enactments of objects, diseases, and species in specific locations, I ask whether it is possible to coordinate enactments across different species bodies and across vastly different spaces. This question has significance for the ‘One Health’ agenda – an interdisciplinary response to diseases shared between humans, animals and the environment. My findings suggest that the current ‘One Health’ framework in Uganda works on an assumption that pathogens are ontologically singular and made visible in the same way by pig supply chain actors, veterinarians, and doctors. I argue that if different enactments are not coordinated in order to make the same disease visible, then ‘One Health’ interventions could continue to neglect an array of neglected zoonotic diseases.